Supplemental oxygen for symptomatic relief in people with serious respiratory illness: a systematic review and meta-analysis - Zainab Ahmadi; Natasha E. Smallwood; Anne-Marie Russell; Ravijyot Saggu; Lorena Romero; Anne E. Holland; Magnus Ekström (European Respiratory Review)
Background People with serious respiratory illness frequently have a high symptom burden and may be prescribed supplemental oxygen therapy with the aims of reducing the severity of breathlessness and improving health-related quality of life (HRQoL). This systematic review and meta-analysis aimed to assess the effectiveness of oxygen therapy versus no oxygen on 1) breathlessness, 2) HRQoL and 3) adverse events. Methods A comprehensive search was performed in Embase, Medline and the Cochrane Central Register of Controlled Trials for randomised controlled trials published prior to June 2022. We used the Cochrane Risk of Bias Tool for appraising the studies and conducted random-effect meta-analyses when appropriate. We pooled effects recorded on different scales as standardised mean differences (SMDs) with 95% confidence intervals. Lower SMDs indicated decreased breathlessness or HRQoL. We assessed the certainty of evidence using the Grading of Recommendations, Assessment, Development and Evaluation framework. Results We found that supplemental oxygen (compared with sham air or no treatment), reduced breathlessness intensity during laboratory exercise testing (SMD −0.75, 95% CI −1.23–−0.28, 12 randomised control trials (RCTs), 245 participants), but had no shown effect on breathlessness measured in daily life (SMD −0.08, 95% CI −0.41–0.26, one RCT, 213 participants) or HRQoL (SMD −0.06, −0.17–0.05, 14 RCTs, 1062 participants). Few or no adverse events related to oxygen therapy were reported. For all the outcomes, the certainty of evidence was low. Conclusions Oxygen improved exertional breathlessness in laboratory-based exercise studies but was not shown to improve breathlessness or HRQoL in daily life.